Model Pelaksanaan dan Evaluasi Asuhan Kebidanan Berkesinambungan dalam Praktik Kebidanan Prodi D.IV Kebidanan - Gita Kostania (Poltekkes Kemenkes Surakarta, 2020)
Background: Continuity of Care (CoC) is a philosophical foundation of midwifery education that can promote the understanding of midwifery students to care for women holistically. In implementing the curriculum of Diploma-IV Midwifery study program, the application of CoC by students is carried out integrated in the implementation of the Comprehensive Community Midwifery Practices. This study aims to describe the implementation model and the results of the evaluation of the application of CoC. Methods: It’s descriptive research study, with subjects 89 people (clients and students) in 7th semester of Diploma-IV Midwifery Study Program of Poltekkes Surakarta. The instruments were in the form of observation guidelines, observation sheets on the results of CoC, satisfaction of care, and achievement of student competencies. Data is presented in verbal and numeric form. Results: The ongoing midwifery care model that is applied refers to the management of the client by a care-provider team (midwives, students and supervisors). The implementation cycle consists of: planning, implementation and evaluation. Outcomes of CoC: there were no complications in labor (91.01%) and newborns (95.51%), client's condition in the postpartum period and breastfeeding was normal (100%). The majority of clients expressed very satisfied with care (73.03%). Evaluation from students, CoC can support the achievement of competencies (93.26%). Conclusion: CoC is carried out by a care provider team in three stages. The application of care has an impact on good delivery outcomes, and for students to support the achievement of competencies.